Ekskrementelle værdier i humaniora og livsvidenskaberne - Viney, William; Berle Hammeken, Morten (Slagmark - Tidsskrift for idéhistorie, 2019)
EXCREMENTAL VALUES IN THE HUMAN AND LIFE SCIENCES This article considers the relationship between human excrement and Western anthropocentrism. It explores philosophical, literary, and scientific texts to describe an historical and creative tendency, linking human excrement to a subject that requires contemplation, governance, or both. The article explores some of the histories that have caused human wastes and the scientific management of subjecthood to intermingle. Despite the emergence of ecological and scientific evidence that indicates the integral immunological and metabolic role played by bacterial life, thinking about human waste as a finite product and process continues to underwrite similarly bounded ideas of self, society, and body. By exploring excremental values that do not depend on a fixed or universal idea of human self-sufficiency, the article makes a modest appeal to develop new vocabularies and a fresh set of narrative forms that can describe life in states of spatial absorbency and temporal co- emergence. Rather than focus on elevating humans above the things they should master but cannot this article asks that we pay closer attention to the beings that bring humans into being.